(untitled) (L’architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2020)
Solomon writes to explore what he regards as the bad design of cities during the past century. He blames the hegemony of modernism, defining modernism as a vain atempt to solve problems through abstract reasoning while ignoring the obvious lessons of history and experience. He argues from examples, not theories. Much of the book is a series of short essays that function as parables. Each of these illustrates the author’s view of a particular issue. He often embodies his argument in the person of one of his heroes (Balanchine, Chanel, Nabokov, many others) or villains (Descartes, Gropius, CIAM, etc.). The result is a wise and entertaining book that falls just short of being a classic. A clue to the problem is the meaningless title “LOVE versus HOPE.” This is the first in a number of such either/or flip cards that occur throughout the text, each presenting a Manichean choice between two opposing visions – sprawl versus erasure, slab block versus perimeter block, etc. We sense that some broader truth may be shared by all these independent conundrums, but the title informs us that if so, it has yet to be articulated.